The pre-S2 domain of the hepatitis B virus is dispensable for infectivity but serves a spacer function for L-protein-connected virus assembly - Ni, Yi; Sonnabend, Jessika; Seitz, Stefan; Urban, Stephan (Journal of virology, 2010)
The envelope of the human hepatitis B virus (HBV) contains three membrane proteins (L, M, and S). They accomplish different functions in HBV infectivity and nucleocapsid envelopment. Infectivity determinants have been assigned to the N-terminal part of the pre-S1 domain of the L protein and the antigenic loop of the S domain in the L and/or S protein. Nucleocapsid envelopment requires a C-terminal sequence within pre-S1, including the five N-terminal amino acids of pre-S2 as part of the L protein. However, the role of the M protein and the pre-S2 domain of the L protein are not entirely understood. We addressed this question and analyzed assembly competence and infectivity of viruses that lack the M protein and, at the same time, carry alterations in the pre-S2 domain of L. These include deletions, in part frameshift mutations and a randomization of virtually the entire pre-S2 sequence. We found that the M protein is dispensable for HBV in vitro infectivity. Viruses that lack the M protein and contain a mostly randomized pre-S2 sequence assemble properly and are infectious in HepaRG cells and primary human hepatocytes. While deletions of 20 amino acids in the pre-S2 domain of L protein allowed the production of infectious virions, more extended deletions interfered with assembly. This indicates that the pre-S2 domain of the L protein serves an important role for virus assembly, presumably as a spacer that supports conformational changes of L protein but does not participate as part of the M protein or as a subdomain of the L protein in virus entry.
Gesehen am 15.05.2023